Implementation of the EFOMP protocol for quality control in digital mammography in a multi-hospital/vendor context. (September 2016) - A.Savini,; Bartolucci, F.; Fidanza, C.; Rosica, F.; Capone, F.; Orlandi, G.
Abstract : Introduction: The European Federation of Organisations in Medical Physics (EFOMP) has recently released a protocol for quality control (QC) in digital mammography with the intent of harmonizing and simplifying the QC procedures across the European countries. Purpose: The aim of this work was to report our experience regarding the implementation of the EFOMP protocol for QC in digital mammography in a multi-hospital/vendor context. Materials and methods: QC tests suggested by the EFOMP protocol were merged with mandatory tests by national (Italian) regulations in order to build a local QC protocol. The protocol was applied to one DR and three CR mammography systems developed by different vendors. Time needed for routine QCs was measured. A fast weekly test was implemented to assess the long term reproducibility of relevant quantities (dose and SNR). Results: By employing one physicist and one technologist, the time needed for routine QC was: 4.5 h ± 0.5 h (annual tests), 2.5 h ± 0.5 h (semiannual tests), 0.2 h ± 0.1 h (weekly tests). For weekly tests, coefficients of variation of dose and SNR were below 6.0% (four-months period evaluated). By applying the developed protocol, two major and five minor anomalies were identified and corrected. Conclusions: The EFOMP protocol could be adapted to local (Italian) regulations with minor modifications. Flexibility and simplification of routine QCs were advantageous in a busy multi-hospital/vendor context. Disclosure: None.